Cervicitis y su relación con EPI en mujeres de 25 a 40 años atendidas por consulta externa en el Centro de Salud N.3 en el periodo mayo - octubre 2014 - Moreno Romero, Pablo Andrés (2015)
The present research was made for determinate the relation that exists between Cervicitis and the Pelvic Inflammatory Disease (P.I.D) in women between 25 and 40 years old treated at the outpatient department of the Health Center of Loja N • 3; and indentify the incidence of these pathologies by age in years, marital status and parity, to determinate if these variables act as risk factors directly and indirectly ways in these diseases.This is a prospective study that included a review of the database of the Health Center of 1060 patients attending the outpatient service between the months of May to October 2014 . After finsishing this research, from the 100% of the sample, it found that 14%, (152 patients) were attended due to suffer Cervicitis, of wich the 54% presented at age of 25 and 30 years old, the 39% that is common in women in free unión, and the 45% are women with history of giving birth for the first time; likewise it was found that from patients with cervicitis, the 20% (30 women) developed Pelvic Inflammatory Disease (P.I.D), from this group the 53% it appeard between the ages of 25 and 30 years old, the 50% is more common in married women, and the 60% are women with history of two births. These results allowed to estimate with accuracy the incidence of cervicitis in our midst and its relation with the Pelvic Inflammatory Disease (P.I.D.), having as reference the variables like age, marital status and the parity between the two entities, to recommend the realization of poblational researchs at a big scale that possibly take us to the implementation of programs of screening at local and national level. Keywords : cervicitis , pelvic inflammatory disease , parity , age , marital status, first birth mother, second birth mother.